THE USE OF DOMINO CARD GAME TO ENHANCE STUDENTS’ VOCABULARY MASTERY - Seri Khairani; Pinmade V. Tampubolon; Danil Sanjaya Nasution; Dani Akbar Harahap; Annisa Putri (J-Shelves of Indragiri (JSI), 2026)
This aims of research are to know: 1) to what extent is the application of domino card game, 2) to what extent the students’ vocabulary mastery before and after using domino card game, 3) whether there is significant effect of using domino card game on students' vocabulary mastery at the eighth grade students of SMP Negeri 9 Padangsidimpuan. This research uses exprimental method with pre-experimental design by one group pretest-posttest design. The population of this research is all of the eighth grade students of SMP Negeri 9 which consist of 168 students. Sample are eighth 5 which consist of students 28 students which taken by porposive sampling. In data collection techniques researcher uses observation sheets and test as an instrument. The results of this research: the using of domono card game is 80% (very good category). The students’ vocabulary mastery before and after using domino card game is 46.14 (poor category), and 78.57 (good category). Hypothesis testing researcher shows the Asymp. Sig. (2-tailed) value was 0.000, lower than the significance level of 0.05 (0.000 < 0.05). So the hypothesis is accepted. It means that, there is significant effect of domino card game on students’ vocabulary mastery at the seventh grade students of SMP Negeri 9 Padangsidimpuan in 2025/2026 Academic Year.